Memory effects in isothermal crystallization. I. Theory - Ziabicki, A.; Alfonso, G.C.
A theoretical analysis of transient isothermal crystallization, including relaxational and athermal effects is given. The analysis is based on Kolmogoroff-Avrami-Evans transformation equation and nucleation theory of Turnbull and Fisher. The memory of previous structures manifests itself in the distribution of atomic (molecular)clusters which determines the initial number of crystal nuclei and the initial rate of thermal nucleation.
Keywords: CRYSTALLIZATION; MEMORY EFFECTS; NUCLEATION; CLUSTER DISTRIBUTION; RELAXATION TIMES